Laparoscopic splenectomy and proximal splenorenal shunt for portal hypertension due to portal vein thrombosis in a patient with protein S deficiency - Alvizuri Gómez, Claudia (2021)
Portal vein thrombosis (PVT) is a rare condition in the general population that develops serious complications if left untreated for long time. We present a case of a 29-year-old woman who developed PVT due to protein S deficiency versus neonatal funiculitis. Over time, the patient developed upper gastrointestinal bleeding due to esophageal varices and hypersplenism with splenic sequestration that caused minor bleeding episodes. Laparoscopic splenectomy and proximal splenorenal shunt with distal pancreatectomy due to aneurysmal dilatations of the splenic artery were successfully performed to avoid mayor progression of portal hypertension. Patient was discharged with indefinite anticoagulation and after surgery platelets raised 3 3 ectomy and proximal splenorenal shunt for portal hypertension due to portal vein ombosis is an adequate surgery procedure which should be applied in these medical cases.